Acute Cholecystitis Treatment - Harmantepe, Ahmet Tarık (General Surgery III, 2023)
The diagnosis and treatment of acute cholecystitis (AC) is constantly evolving and advancing. The diagnosis of AC can be easily made by physical examination, laboratory findings and radiological methods. However, if the treatment process is not managed well, it can result in disaster. Although the gold standard is laparoscopic cholecystectomy (LC), new alternative treatments are developing. There is ongoing debate in the medical community regarding the optimal timing for surgical intervention in cases of acute cholecystitis. The general approach is to perform LC within 72 hours in acute cholecystitis, with the most preferred approach. Discussions are ongoing in the literature to determine the ideal timing for surgical intervention in patients with acute cholecystitis (AC). In the past, patients who had symptoms for over 72 hours were given antibiotics and the cholecystectomy (LC) was postponed for 4-6 weeks to allow the inflammation to reduce. However, recent evidence suggests that this approach may not be the best option, as it has been shown that length of stay, morbidity, and overall health care costs can be reduced even in patients with AC and LC symptoms lasting more than 72 hours. Additionally, the use of less invasive gallbladder drainage methods, such as percutaneous cholecystostomy (PC) and endoscopic methods, need to be further evaluated as these may provide a temporary solution for high-risk patients who are not suitable for surgery. These methods, however, may result in higher re-hospitalization rates in the future.